Penerapan Metode Single Moving Average Dalam Peramalan Persediaan Bahan Pangan - Kukuh Rizqi Liyadi; Heny Pratiwi; Pitrasacha Aditya; Muhammad Ibnu Sa’ad (LPPM STIKOM Tunas Bangsa, 2022)
Forecasting is a technique that is quite widely used today and has been developed since the 19th century. In line with the development of increasingly sophisticated forecasting techniques accompanied by developments in the use of computers. Forecasting can predict or estimate what will happen in the future using certain techniques so that forecasting has received increasing attention in recent years. Web-based applications are one of the systems that support the development of computer use, therefore in this study, researchers develop web-based applications for forecasting using the Single Moving Average method. In this study, forecasting was carried out using the Single Moving Average method to find out how much food is needed in the following month based on actual data from the previous months. Based on forecasting which was carried out using actual data from December 2021 to June 2022, the results obtained in the following month, namely July 2022, were 2,901 kg.